Monitoring performance through Dashboards - Maria Ines Paraiso Vieira; Laureano, Raul M. S.; Pedrosa, I. (2018 13th Iberian Conference on Information Systems and Technologies (CISTI), 2018)
The information and the way we use it are the key for an efficient implementation of a management procedure. It is imperative that information is delivered promptly, in a layout accessible to everyone. This way, the concept Indicators of Performance and Dashboards has been created. It concerns a visual imperative technique for information analysis and decision support. Ten interviews were conducted with managers and employees of accounting and auditing companies to understand the state of knowledge and use of the concepts. Thus, eight indicators have emerged that complement the strategic dashboard, addressed to management. This study contributes to expand the managers' knowledge in accounting and audit sectors about development evaluation through dynamic tools like the dashboard. It allows the management to access a daily life support tool and the monitoring and realization of their goals.